Visualization of Carbon Footprint Value Calculation from Residential Activities In The Energy and Transportation Sector In Jombang District Community - Nadila, Marcelina Putri; Zulfikar, Zulfikar (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
This study aims to visualize the calculation of carbon footprint value generated from settlement activities in the energy and transportation sectors in the Jombang Sub-district community. The method used is quantitative with primary data collection through questionnaires and direct surveys and secondary data from related agencies. The analysis was conducted to calculate carbon emissions from using electricity, LPG, and motor vehicle fuel (gasoline and diesel). The results show that household energy consumption produces carbon emissions of 1,200 tons of CO2e per year, while the transportation sector contributes 800 tons of CO2e per year. Total carbon emissions from both sectors reached 2,000 tons of CO2e per year in Jombang Subdistrict. Data visualization was conducted using graphical software to facilitate public understanding of the impact of daily activities on the environment. The findings are expected to serve as a basis for developing more sustainable local policies and encouraging community participation in carbon emission reduction efforts. With this visualization, the community will be more aware of the importance of reducing carbon footprints to achieve a healthier and more sustainable environment.